Enseñar en los márgenes: las representaciones sociales de profesoras que se desempeñan en contextos de pobreza en La Matanza - Buenos Aires (Revista Peruana de Investigación Educativa, 2022)
This work investigates the incidence of social representations in the practice of secondary school teachers in contexts of poverty in La Matanza, Buenos Aires, in order to reflect on whether and how they affect the reproduction of educational inequalities. To carry it out, a qualitative study was conducted with in-depth interviews with teachers who teach in schools attended by young people from vulnerable sectors. In them, the representations that teachers express about these institutions, their students and their practice were observed. The results show that teachers working in schools attended by students from low-income families tend to give priority in their work to the pedagogical bond over to pedagogical-curricular issues and to evaluate the "student's job" rather than the assimilation of contents, which are also simplified. In addition, they tend to assume tasks of care and support, and to have low expectations of students. Therefore, it is important to understand this phenomenon in greater depth in order to take measures that offer students a more enriching educational experience.
Keywords: Social representations; Teachers; Educational inequality; Poverty; Secondary education